Online Learning Problems; Students' English Learning Barriers - Muhamad Alfi Khoiruman; Adib Ahmada (Darussalam English Journal (DEJ), 2021)
Policies related to online learning which were then simultaneously used as a learning system did not appear without problems. As a result, countries that are not ready with this system, of course, face many problems, especially for teaching staff and students. This study, tries to explore problems that have the potential to hinder students' understanding during online learning, which means that researchers will only focus on obstacles in the learning process, both internal to students and external from teachers and parents, not technical matters such as network constraints, no quota and other related matters. Subjects in this study were 15 junior high school students in Penan, Pejarakan, Ampenan. Qualitative research with this descriptive approach, in the process using Observation and Interview methods as the main way to obtain data where the results of this study classify the main problems that arise into 3 parts, namely; 1) There is a delay from the subject in participating in online class activities, 2) There is a tendency not to take learning activities seriously by doing other activities such as playing games, watching TV and other activities and 3) the lack of time and the ability of companions during the learning process is good because they do not have sufficient understanding of the material or other activities or work to be undertaken.